Prenatal diagnosis of aberrant right subclavian artery in an unselected population - Song, Mi Jin; Han, Byoung Hee; Kim, Young-Hwa; Yoon, So Young; Lee, Yoo Mi; Jeon, Hye Su; Park, Bo Kyung (Ultrasonography (Seoul, Korea), 2017)
The purpose of this study was to determine the frequency of aberrant right subclavian artery (ARSA) among unselected fetuses and to evaluate its association with chromosomal abnormalities and other congenital anomalies. In all, 7,547 fetuses (gestational age, 20 to 34 weeks) were examined using routine antenatal sonography at our institution between April 2014 and September 2015. The right subclavian artery was assessed using grayscale and color Doppler ultrasonography in the transverse 3-vessel and tracheal view, and confirmed in the coronal plane. ARSA was found in 28 fetuses (0.4%). Further, 27 of these 28 fetuses were euploid (96.4%). Trisomy 18 was the only chromosomal anomaly (3.6%) found in the study sample. ARSA was an isolated finding in 23 of the 28 cases (82.1%). In the remaining three cases (10.7%), ARSA was accompanied with extracardiac anomalies. Other cardiac defects were present in three cases (10.7%). Isolated ARSA does not seem to be associated with a significantly increased risk of aneuploidy. However, the possibility of fetal karyotyping, which is a more invasive procedure, should be discussed in the light of the overall risk of the fetus.